Peer victimization and children’s internet addiction in China: a moderated mediation model - Pingyan Zhou; Pingyan Zhou; Jinping Cai; Jiaxin Cui; Jian Liu; Wenguang He; Cai Zhang; Fumei Chen; Zhe Wang (Frontiers in Psychology, 2023)
BackgroundPeer victimization used to be considered as a crucial risk factor for children addicted to the internet. Whereas some victimized ones are function better than would be expected. Variability across individuals indicates that it is necessary to understand how children cope with being bullied and why they do not exhibit maladaptive outcomes.ObjectiveWe explored the underlying mechanisms by testing whether subjective well-being was a mediator between peer victimization and Internet addiction and whether the mediation effects conditioned on the levels of parent–child relationship (PCR).MethodsData were collected from 65, 868 elementary school students in China (Mage = 9.56 years, SD = 0.62, 54.0% male) using four questionnaires.ResultsWe found that: (1) subjective well-being can partially mediate the relationship of the two variables; and (2) PCR can moderate direct path and second half of the intermediary process. These moderating effects were stronger for children with higher PCR vs. lower PCR, as a strong PCR can help children to deal with intense emotions and to access effective resources to obtain support.ConclusionThis study deepens our understanding of how peer victimization leads to internet addiction, identifies a supportive PCR as a crucial factor that strengthens the resilience of child victims, and highlights the value of focusing on improving the relationship between parents and children in intervening internet addiction related to peer victimization.